(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1989)
Undatable hut-circle associated with field-walls; decorated stone, clay loomweight. Earlier occupation layer and post-hole were associated with plain pottery of the late 2nd or early 1st millennium BC. A R